2022
DOI: 10.3390/cells11060925
|View full text |Cite
|
Sign up to set email alerts
|

Unbridled Integrons: A Matter of Host Factors

Abstract: Integrons are powerful recombination systems found in bacteria, which act as platforms capable of capturing, stockpiling, excising and reordering mobile elements called cassettes. These dynamic genetic machineries confer a very high potential of adaptation to their host and have quickly found themselves at the forefront of antibiotic resistance, allowing for the quick emergence of multi-resistant phenotypes in a wide range of bacterial species. Part of the success of the integron is explained by its ability to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 103 publications
(141 reference statements)
0
24
0
Order By: Relevance
“…Therefore, the very stress that induces the expression of the integrase allows the screening for a set of cassettes that may in turn enable the cell to escape from it. For this reason, integrons are described as “on demand” adaptation systems [9,10].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the very stress that induces the expression of the integrase allows the screening for a set of cassettes that may in turn enable the cell to escape from it. For this reason, integrons are described as “on demand” adaptation systems [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Remarkably, we previously found that the integrase, which catalyze the cassette shuffling, is part of the SOS regulon 8 . For this reason, integrons are described as "on demand" adaptation systems 9,10 . The integron integrase (IntI) has a very singular place among the broad family of the tyrosine recombinases 11 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tese may have lost gene cassettes in the absence of antimicrobial selective pressure or on the other hand, never acquired the resistance gene insert [48]. However, they can acquire new resistance genes and facilitate the dissemination of resistance in bacteria [13].…”
Section: Integrons In Fish-livestock Integrated Farmsmentioning
confidence: 99%
“…Genetic elements, such as plasmids, transposons, and integrons, can be transferred horizontally between bacteria of diferent origins. Integrons are especially important among these genetic elements given their ability to capture and express resistance genes harbored by diferent gene cassettes [13]. Class 1 integrons, the most common integrons, have a complete structure containing a 5′-conserved segment, variable gene cassettes, and 3′-conserved segment.…”
Section: Introductionmentioning
confidence: 99%